The Role of Mitochondria in the Dual Effect of Low-Temperature Plasma on Human Bone Marrow Stem Cells: From Apoptosis to Activation of Cell Proliferation - Sergej V. Belov; Yakov P. Lobachevsky; Yurij K. Danilejko; Aleksej B. Egorov; Alexander V. Simakin; Alireza Maleki; Andrey A. Temnov; Mikhail V. Dubinin; Sergey V. Gudkov (Applied Sciences, 2020)
The potential use of low-temperature plasma (LTP) for therapeutic purposes has aroused the concern of many researchers. This paper examines the effect of LTP on the morphofunctional state of human bone marrow stem cells (BMSC). It has been established that LTP-induced oxidative stress has a dual effect on the state of stem cells. On the one hand, a cell culture exposed to LTP exhibits the progression of a destructive processes, which is manifested by the perturbation of the cell’s morphology, the initiation of lipid peroxidation and the accumulation of products of this process, like diene conjugates and malondialdehyde, as well as the induction of mitochondrial dysfunction, leading to cell death. On the other hand, the effect of LTP on BMSC located at a distance from the plasma is accompanied by the activation of proliferative processes, as evidenced by the tendency of the activity of mitochondrial biogenesis and fission/fusion processes to increase. The paper discusses the role of mitochondria and reactive oxygen species (ROS) in the cellular response to LTP.